Impaired robust interhemispheric function integration of depressive brain from REST‐meta‐MDD database in China. (20th March 2022) - Deng, Ke; Yue, Ji‐Hui; Xu, Jian; Ma, Ping‐Ping; Chen, Xiao; Li, Le; Bai, Tong‐Jian; Bo, Qi‐Jing; Cao, Jun; Chen, Guan‐Mao; Chen, Ning‐Xuan; Chen, Wei; et al.
Abstract: Background: Recently, functional homotopy (FH) architecture, defined as robust functional connectivity (FC) between homotopic regions, has been frequently reported to be altered in MDD patients (MDDs) but with divergent locations. Methods: In this study, we obtained resting‐state functional magnetic resonance imaging (R‐fMRI) data from 1004 MDDs (mean age, 33.88 years; age range, 18–60 years) and 898 matched healthy controls (HCs) from an aggregated dataset from 20 centers in China. We focused on interhemispheric function integration in MDDs and its correlation with clinical characteristics using voxel‐mirrored homotopic connectivity (VMHC) devised to inquire about FH patterns. Results: As compared with HCs, MDDs showed decreased VMHC in visual, motor, somatosensory, limbic, angular gyrus, and cerebellum, particularly in posterior cingulate gyrus/precuneus (PCC/PCu) (false discovery rate [FDR] q < 0.002, z = −7.07). Further analysis observed that the reduction in SMG and insula was more prominent with age, of which SMG reflected such age‐related change in males instead of females. Besides, the reduction in MTG was found to be a male‐special abnormal pattern in MDDs. VMHC alterations were markedly related to episode type and illness severity. The higher Hamilton Depression Rating Scale score, the more apparent VMHC reduction in the primary visual cortex. First‐episode MDDs revealed stronger VMHC reduction in PCu relative to recurrent MDDs. Conclusions: We confirmed a significant VMHC reduction in MDDs in broad areas, especially in PCC/PCu. This reduction was affected by gender, age, episode type, and illness severity. These findings suggest that the depressive brain tends to disconnect information exchange across hemispheres.